HISTOPHATOLOGICAL CHANGES IN HEPAR OF WHITE RATS GIVEN ETHANOL EXTRACT OF ANT NEST AND GENTAMICIN - Muda, Gde Jasmara; Arjana, Anak Agung Gde; Berata, I Ketut; Merdana, I Made (Buletin Veteriner Udayana; Vol. 12 No. 1 Pebruari 2020DO - 10.24843/bulvet.2020.v12.i01.p02, 2020)
This study aims to evaluate that the administration of ant nest reduces the side effects of toxic doses of gentamicin seen from the histopathological changes in hepar of white rats ( Rattus norvegicus ). This study used 24 male white rats, divided into four treatment groups, namely negative controls (P0) there were only given food and drink, positive controls (P1) administered gentamicin at a dose of 100mg/kgBB intraperitoneally for 10 days. The group (P2) was given gentamicin 100mg/kgBB intraperitoneally and ant nest extract with a dose of 250mg/kgBB orally for 10 days. The group (P3) was given 250mg/kgBB of ant nest extract for 7 days, after which ant nest extract was given at a dose of 250mg/kgBB and gentamicin with a dose of 100mg/kgBB intraperitoneally for 10 days.White rat hepar was taken and processed for making histopathological preparations, with hematoxylin eosin (HE) staining. The results showed that there was a significant difference between negative control and positive control groups. The mean score of improvement in hepar damage of white rats was significantly different between treatment P1, P2 and P3. The P2 and P3 groups that showed the most change near the mean score of the negative control group. Giving ant nest extracts to white rats for 17 days at a dose of 250mg/kgBB can improve the side effects of the administration of gentamicin 100mg/kgBB in the hepar of white rats.